Executive Stock Option Scheme (ESOS) and blockholder ownership as governance mechanisms on firm performance / Ahmad Ibn Ibrahimy - Ibrahimy, Ahmad Ibn (2012)
The Asian Crisis of late 1990s has highlighted the problems of corporate governance in South-East Asian corporations. These corporations, especially in Malaysia, are characterized by concentrated ownership with the existence of poor corporate governance structure. Thus, separation of ownership and control may lead to agency conflicts between the majority and minority shareholders in this region rather than the classical agency problem between managers and shareholders. Therefore, there is a need for applying proper corporate governance mechanism tools to alleviate this agency problem that gradually exploits firm performance. This study investigates the effects of two governance mechanism tools, namely Executive Stock Option (ESO) Granting and Blockholders, on Malaysian non-financial companies and how they affect firm performance. The pattern of ESO exercising behavior of Malaysian executives is also taken into consideration. Besides, any time preferences and firm’s size effects on ESO granting are examined to verify the actual motives of adopting ESOs. Finally, the study also explores industry effects of companies which contribute to firm performance.